Kualitas dan Produksi Vermikompos Menggunakan Cacing African Night Crawler (Eudrilus eugeniae): Quality and Production of Vermicompost Using African Night Crawler Worms (Eudrilus eugeniae) - Fahrizal Hazra; Nabila Dianisa; Rahayu Widyastuti (Jurnal Ilmu Tanah dan Lingkungan, 2018)
Adding organic fertilizer such as vermicompost can be done to overcome the deficiency problem of soil organic matter. One of the worm species which can be used in vermicomposting is Eudrilus eugeniae. Purpose of this research was to know how the combination of cow dung and rice straw impacts vermicompost quality from organic carbon, N, P, total K, urease enzyme activity and vermicompost production. Treatment that used in this research is randomized completely design with 4 treatments. The treatments are P1: feed 400 g of cow dung, P2: feed 400 g of rice straw, P3: feed 280 g of cow dung and 120 g of rice straw, and P4: feed 140 g of cow dung and 60 g of rice straw. The research result shows that real treatment impacts all parameters on the produced vermicompost. Production result is determined by ratio value of output/input (O/I). Quality and production of vermicompost on P4 is a treatment with the best result. It is because the combination of cow dung and rice straw gives a relatively complete macro nutrient result and the higher feed dose will gives higher vermicompost production.